14 Correlation between arterial stiffness using oscillometry and cardiovascular magnetic resonance in a population with heart failure with preserved ejection fraction (HFpEF). (March 2019) - Athithan, Lavanya; Athithan, L; Kanagala, P; Chan, DCS; Singh, A; Gulsin, GS; Graham-Brown, MPM; McAdam, J; Marsh, A; Parke, K; Wormleighton, J; Arnold, JR; et al.
Abstract : Background: Arterial stiffness has been implicated in the pathophysiology of Heart Failure with Preserved ejection fractions (HFpEF). Stiffness can be measured by a variety of methods, and there is significant evidence (Class 1, Level of Evidence A) to support the use of carotid femoral pulse wave velocity (cfPWV) based on population studies. Cardiovascular Magnetic resonance imaging (CMR) allows a direct measure of aortic stiffness (distensibility) and also aortic PWV. Purpose: To compare PWV measures by oscillometry (cfPWV) against CMR PWV and to correlate both with aortic distensibility measured by CMR. Methods: We recruited 140 patients with HFpEF who underwent VICORDER® assessment of cfPWV and a multiparametric CMR which included cine imaging of the ascending descending aorta at the level of the pulmonary artery bifurcation and high temporal resolution through-plane phase contrast flow sequence (typical parameters: slice thickness 5 mm, VENC 250 cm/s, reconstructed to 100–128 phases, temporal resolution ∼10 ms, TE 4 ms, matrix 176 × 256) planned perpendicular to the thoracic aorta. Aortic (Ao) distensibility was calculated using the formula Distensibility = (Ao max – Ao min)/(Ao min x pulse pressure). CMR PWV was analysed using Java Image Manipulation (JIM) using an overlay technique of the flow curves to calculate time and distance travelled. Results: Of the 140 patients, 86 had both VICORDER® and CMR PWV. Baseline characteristics are listed in Table 1 . Average PWV measured by VICORDER® (Mean 9.79±2.38) and CMR (Mean 9.47±4.05) were similar but there was no significant correlation between the 2 techniques (r=0.04 p=0.73; ICC=0.033, p=0.378). A Bland-Altman plot (figure 1 ) was performed. There was a significant inverse correlation between pulse wave velocity measured by VICORDER® and aortic distensibility of both the ascending (R=−0.44 p<0.001) and descending (R=−0.33 p=0.004) aorta but not for CMR PWV (R=−0.003, p=0.98) and (R=−0.07, p=0.56) respectively. Conclusions: PWV measured using phase contrast CMR and cfPWV measured by oscillometry gave similar mean population values but there was no agreement between the techniques inindividual patients. Therefore, PWV cannot be used interchangeably.